Análisis, diseño y pruebas de hacking ético sobre la infraestructura institucional de la Superintendencia de Control del Poder de Mercado - Paillacho Pozo, Paúl Adonías (2016)
The present work comprises the analysis, design and of ethical hacking tests on the institutional infrastructure of the Superintendencia de Control del Poder de Mercado was performed to contribute with to research the solutions against to latent vulnerabilities in its technological infrastructure. The report is going to be a tool with which to implement policies and actions to mitigate vulnerabilities and work on security; OWASP provide a formal framework with different stages of testing ethical hacking methodology. The introduction of the document have the project definition, the general and specific objectives, methodological framework. The first chapter presents an introduction to computer security and a theoretical framework of the methodology used. In the second chapter describes the initial situation of the Superintendencia de Control del Poder de Mercado and gathering information in the first stage of penetration testing. The third chapter contains the work of enumeration vulnerabilities. In the fourth chapter contains the activities undertaken attack, conclusions, and recommendations